Organizational Culture, Teamwork, and Work Motivation on Employee Performance: Evidence from BPJS Kesehatan - Adrika Wendi; Nancy Yusnita; Widodo Sunaryo (UTSAHA: Journal of Entrepreneurship, 2026)
This study investigates the direct and indirect effects of organizational culture and teamwork on employee performance, with work motivation as a mediating variable. A quantitative survey was conducted with 197 employees from BPJS Kesehatan Head Office, Indonesia, using validated questionnaires measuring organizational culture (33 items, α=0.906), teamwork (38 items, α=0.936), work motivation (35 items, α=0.936), and employee performance (37 items, α=0.942). Path analysis revealed that organizational culture significantly predicted employee performance (β=0.250, p<0.001) and work motivation (β=0.384, p<0.001). Teamwork significantly influenced employee performance (β=0.256, p<0.001) and work motivation (β=0.388, p<0.001). Work motivation exhibited the strongest direct effect on employee performance (β=0.365, p<0.001). Sobel tests confirmed significant mediation effects of work motivation on the relationship between organizational culture and employee performance (z=6.729, p<0.001), and between teamwork and employee performance (z=6.667, p<0.001). These findings demonstrate that work motivation serves as a crucial psychological mechanism through which organizational culture and teamwork influence employee performance. The results validate the Integrative Model of Organizational Behavior within a non-Western public sector context and provide evidence-based recommendations for performance enhancement strategies emphasizing integrated interventions targeting culture, teamwork, and motivation simultaneously.